Writing well in the 21st century : the five essentials - Spencer, Linda, 1943- (Rowman and Littlefield, 2014)
"This guide provides students, career-builders, and professional writers with the basic elements needed for writing in the 21st century. It fully explains, and links, the five essentials of good writing: punctuation, grammar, fact-checking, style, and voice. Throughout history technology has changed both language and writing. Today in the digital age, language and writing are changing at a phenomenal pace. Students, career-builders, and professional writers need this guide that reviews those changes and connects the essentials for creating good writing in the digital age. The book gives writers the tools needed today. Among other essentials, the book: Resolves comma issues by explaining the Open and Close Punctuation systems (writers select which system to use in their writing) ; Clarifies active and passive voice verbs and advocates using strong, specific verbs in writing ; Provides guidelines for choosing credible online websites when searching for resources ; Examines attributes of essentials that contribute to a writing style and urges a critical review of verbs ; Connects elements that combine to create a voice in a written piece. Overall this guide gives readers the basics they need to know to create well-written documents for school, work and in their professional writing."--